Enhancing students’ listening skill through podcasts - Oktavia Widiastuti (UPT P2M Politeknik Negeri Malang, 2012)
Applying podcast as an appropriate multimedia can be very potential and practical as a tool to enhance listening skill. Students and teachers can download podscast easily and freely as source of their listening materials. Listening materials presented through Podcast is possible to increase students’ listening skill as Podcast provides students with authentic and contextual material. Podcast offers an ideal tool for the creative expression of knowledge preferred by today's students, and provides an exciting way for students and teachers to explore and discover listening content or material. Podcasts are particularly suited for extensive listening, for the purpose of motivating students’ interest in listening to English and providing them with exposure to native speakers’ speech (Rost, 1991). Stanley (2006) points out that podcasts offer students a wide range of possibilities for extra listening both inside and outside of the classrooms. The outside classroom listening activity effectively bridges the gap between the formal English which dominates most English language classrooms and the informal English used in real-life communication events. Podcast as a new technology has huge potential in enhancing students’ listening skill. The ease of downloading podcasts to MP3 players and iPods means that students can now engage in plenty of listening practice in any condition.